A lipidomics approach in the characterization of zika-infected mosquito cells: Potential targets for breaking the transmission cycle - Melo, Carlos Fernando Odir Rodrigues; De Oliveira, Diogo Noin; De Oliveira Lima, Estela; Guerreiro, Tatiane Melina; Esteves, Cibele Zanardi; Beck, Raissa Marques; Padilla, Marina Aiello; Milanez, Guilherme Paier; Arns, Clarice Weis; Proença-Modena, José Luiz; Souza-Neto, Jayme Augusto [UNESP]; Catharino, Rodrigo Ramos (Public Library of Science (PLoS), 2016)
Recent outbreaks of Zika virus in Oceania and Latin America, accompanied by unexpected clinical complications, made this infection a global public health concern. This virus has tropism to neural tissue, leading to microcephaly in newborns in a significant proportion of infected mothers. The clinical relevance of this infection, the difficulty to perform accurate diagnosis and the small amount of data in literature indicate the necessity of studies on Zika infection in order to characterize new biomarkers of this infection and to establish new targets for viral control in vertebrates and invertebrate vectors. Thus, this study aims at establishing a lipidomics profile of infected mosquito cells compared to a control group to define potential targets for viral control in mosquitoes. Thirteen lipids were elected as specific markers for Zika virus infection (Brazilian strain), which were identified as putatively linked to the intracellular mechanism of viral replication and/or cell recognition. Our findings bring biochemical information that may translate into useful targets for breaking the transmission cycle.